Substructure-sensitive crystal plasticity with material-invariant parameters - Dindarlou, Shahram; Castelluccio, Gustavo M. (Elsevier, 2022)
Even though crystal plasticity models have been available for decades, the quantification of material parameters is still a matter of debate. Polycrystalline experimental results can normally be reproduced by multiple sets of parameters, raising concerns about the best parameterization to predict the grain-level response. This work presents a novel physics-based crystal plasticity model based on mesoscale dislocation substructures, which are used to characterize material parameters independently. We employ a unique set of parameters with known uncertainty to reproduce the mechanical response of FCC single- and poly-crystals. We demonstrate that mesoscale parameters are material-invariant and can be used to model FCC metals with similar dislocation substructures such as for Cu, Ni and Al. Furthermore, the model is validated by comparing to experimental single- and poly-crystalline stress–strain curves and mesoscale dislocation substructure images. This novel modeling approach is intrinsically designed to predict the response of materials with similar dislocation substructures without the need of single crystal experimental data for calibration.
Keywords: Dislocation substructures; Crystal plasticity; Mesoscale material-invariant parameterization; Single crystals